Genetic micro-epidemiology of malaria in Papua Indonesia: Extensive P. vivax diversity and a distinct subpopulation of asymptomatic P. falciparum infections - Pava, Z; Noviyanti, R; Handayuni, I; Trimarsanto, H; Trianty, L; Burdam, F; Kenangalem, E; Utami, R; Tirta, Y; Coutrier, F; Poespoprodjo, J; Price, R; et al. (Public Library of Science, 2017)
Background: Genetic analyses of Plasmodium have potential to inform on transmission dynamics, but few studies have evaluated this on a local spatial scale. We used microsatellite genotyping to characterise the micro-epidemiology of P. vivax and P. falciparum diversity to inform malaria control strategies in Timika, Papua Indonesia. Methods: Genotyping was undertaken on 713 sympatric P. falciparum and P. vivax isolates from a cross-sectional household survey and clinical studies conducted in Timika. Standard population genetic measures were applied, and the data was compared to published data from Kalimantan, Bangka, Sumba and West Timor. Results: Higher diversity (HE = 0.847 vs 0.625; p = 0.017) and polyclonality (46.2% vs 16.5%, p<0.001) were observed in P. vivax versus P. falciparum. Distinct P. falciparum substructure was observed, with two subpopulations, K1 and K2. K1 was comprised solely of asymptomatic infections and displayed greater relatedness to isolates from Sumba than to K2, possibly reflecting imported infections. Conclusions: The results demonstrate the greater refractoriness of P. vivax versus P. falciparum to control measures, and risk of distinct parasite subpopulations persisting in the community undetected by passive surveillance. These findings highlight the need for complimentary new surveillance strategies to identify transmission patterns that cannot be detected with traditional malariometric methods.